Pirate Life: measuring success through the balanced score card - Slaman, Matthew (2018)
The current work project was brought forth in order to understand and measure the performance/success of an entrepreneurial venture, Pirate Life: Children’s Theatre in Toronto, Canada. The Balance Score Card (BSC) was selected as the appropriate tool for this analysis to simply end effectively outline the major streams of the organization and organize them in a manner that would demonstrate success and areas needing improvement – providing the management with a calibration tool for future years to come.